Pollination in the campo rupestre: A test of hypothesis for an ancient tropical mountain vegetation - Monteiro, Beatriz Lopes [UNESP]; Camargo, Maria Gabriela Gutierrez [UNESP]; Loiola, Priscilla De Paula [UNESP]; Carstensen, Daniel Wisbech; Gustafsson, Simone; Morellato, Leonor Patrícia Cerdeira [UNESP] (Oxford University Press (OUP), 2021)
The campo rupestre is a Neotropical OCBIL (old, climatically buffered infertile landscape), a grassy-shrub vegetation with high species richness and endemism, characterized by rocky outcrops surrounded by grasslands distributed in South American ancient mountaintops. We tested one OCBIL prediction: the prevalence of long-distance pollinators ensuring cross-pollination across the archipelago-like landscapes of the campo rupestre. We described the pollination systems and tested whether their frequency differed across vegetation types and elevation, focusing on long-distance systems. We performed non-systematic and systematic surveys of plants and plant-pollinator interactions across the elevation gradient and vegetation types. We also reviewed the literature on campo rupestre pollination and applied an accuracy criterion to infer 11 pollination systems. The bee system was split into large bee (long-distance) and small bee (shorter distances) to test the prevalence of long-distance pollination systems. We surveyed 413 pollinator species, mostly bees (220) and flies (69). Among the 636 plant species studied, the bee pollination system was dominant (56%), followed by wind and hummingbird. Wind, small-bee and fly pollination systems increased with elevation, and small-bee and wind pollination systems prevailed in grasslands. Large-bee and hummingbird long-distance pollination systems remained unchanged with elevation and were more frequent in the highly isolated rocky outcrops corroborating the OCBIL theory.
Keywords: Espinhaço Range; long distance pollinators; OCBIL; pollination systems; rocky outcrops; rupestrian grassland; Serra do Cipó; The James Effect